A DFT approach to discriminate the antagonist and partial agonist activity of ligands binding to the NMDA receptor. (1st February 2018) - Haslak, Zeynep Pinar; Bozkurt, Esra; Dutagaci, Bercem; De Proft, Frank; Aviyente, Viktorya; De Vleeschouwer, Freija
ABSTRACT: The activation of N-methyl-D-aspartate receptors is found to be intimately associated with neurodegenerative diseases which make them promising therapeutic targets. Despite the significantly increasing multidisciplinary interests centred on this ionotropic channel, design of new ligands with intended functional activity remains a great challenge. In this article, a computational study based on density functional theory is presented to understand the structural factors of ligands determining their function as antagonists and partial agonists. With this aim, the GluN1 subunit is chosen as being one of the essential components in the activation mechanism, and quantum chemical calculations are implemented for 30 antagonists and 30 partial agonists known to bind to this subunit with different binding affinities. Several quantum chemical descriptors are investigated which might unlock the difference between antagonists and partial agonists. Abstract :